POLIGAMI LEBIH DARI EMPAT DALAM PERSPEKTIF FIQIH ISLAM DAN UNDANG-UNDANG NOMOR 1 TAHUN 1974 - DYAH SEPTARI MARITO SIREGAR (PREMISE LAW JURNAL, 2016)
Polygamy is as marriage between a man and two or more women (four women in maximum); it has legal ground in the Islamic law. The study used judicial normative and descriptive methods. The result of the study showed that the implementation of polygamy in the Islamic society is violated since many men have more than four wives, and it is contrary to the provisions in the Islamic Fiqh, KHI (Compilation of the Islamic laws), and Law No. 1/1974 on Marriage . Its legal consequence is that the marriage is considered as adultery or an illegitimate marriage. Children who are born from polygamy of more than four wives are also considered as illegitimate children. They do not have any nasab (lineage) with their father or his descendant although they become the responsibility of their biological parents. Keywords: Marriage, Polygamy, Fiqh, UUP (Marriage Law)